2023
DOI: 10.3390/ijms24032296
|View full text |Cite
|
Sign up to set email alerts
|

Tenebrio molitor as a Simple and Cheap Preclinical Pharmacokinetic and Toxicity Model

Abstract: The progression of drugs into clinical phases requires proper toxicity assessment in animals and the correct identification of possible metabolites. Accordingly, different animal models are used to preliminarily evaluate toxicity and biotransformations. Rodents are the most common models used to preliminarily evaluate the safety of drugs; however, their use is subject to ethical consideration and elevated costs, and strictly regulated by national legislations. Herein, we developed a novel, cheap and convenient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Both beetles are easy to rear under controlled conditions, and their genome have been sequenced in recent years (Kaur et al 2023 ; Oppert et al 2023 ; Richards et al 2008 ). For these reasons, they are useful model species (Brai et al 2023 ; Brown et al 2009 ; Campbell et al 2022 ) for genetic (Suzuki et al 2008 ), physiological, immunological (Abdel-Latief and Hoffmann 2014 ; Park et al 2014 ; Vigneron et al 2019 ; Vommaro et al 2021 , b ), developmental, behavioural (Pai and Bernasconi 2008 ) and evolutionary (Pointer et al 2021 ) studies. In addition, both species are used to address the effects of pesticides (Kostaropoulos et al 2001 ; Pedersen et al 2020 ), applied to control populations infesting food commodities (Arthur et al 2019 ; Ntalli et al 2021 ; Tungjitwitayakul et al 2022 ), including insect resistance (Campbell et al 2022 ; Rösner et al 2020 ) and in terms of ecotoxicological effects (Naccarato et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both beetles are easy to rear under controlled conditions, and their genome have been sequenced in recent years (Kaur et al 2023 ; Oppert et al 2023 ; Richards et al 2008 ). For these reasons, they are useful model species (Brai et al 2023 ; Brown et al 2009 ; Campbell et al 2022 ) for genetic (Suzuki et al 2008 ), physiological, immunological (Abdel-Latief and Hoffmann 2014 ; Park et al 2014 ; Vigneron et al 2019 ; Vommaro et al 2021 , b ), developmental, behavioural (Pai and Bernasconi 2008 ) and evolutionary (Pointer et al 2021 ) studies. In addition, both species are used to address the effects of pesticides (Kostaropoulos et al 2001 ; Pedersen et al 2020 ), applied to control populations infesting food commodities (Arthur et al 2019 ; Ntalli et al 2021 ; Tungjitwitayakul et al 2022 ), including insect resistance (Campbell et al 2022 ; Rösner et al 2020 ) and in terms of ecotoxicological effects (Naccarato et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Azevedo et al [98] measured the protective effects of Peumus boldus and Matricaria chamomilla teas on T. molitor larvae, after the induction of oxidative stress by LPS. In their recent study, Brai et al [99] analyzed the toxicity of drugs with different pharmacological applications (antibiotics, neuroleptics, analgesics, antihistamines, and anti-inflammatories) in T. molitor and observed that the insect could be used as an efficient alternative for evaluating the acute toxicity of compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The median lethal dose (LD 50 ) was determined for compound 17 in a Tenebrio molitor coleoptera (TMC) toxicity model published previously [33]. Due to ethical reasons, and according to the 3Rs principle, the insect model was preferred to the murine model to preliminarily evaluate the potential in vivo toxicity.…”
Section: In Vivo Toxicitymentioning
confidence: 99%